Effectiveness of Online System Lectures during the Covid-19 Pandemic - Arhas, Sitti Hardiyanti; Mahardika, Lifya Ainun; Darwis, muhammad; Zainuddin, M. Said (Pinisi Journal of Education and Management, 2022)
The effectiveness of online learning is one form of measuring the success of an online-based learning process in achieving learning objectives. The purpose of this study is to find out how effective online learning is and the factors that support and hinder online learning during the Covid-19 Pandemic in the Office Administration Education Study Program, Faculty of Social Sciences and Law, Makassar State University. To find out the purpose of this research, a qualitative descriptive research was used. There were 10 informants in this study using data collection techniques through observation, interviews, and documentation. The data obtained from the research results are then processed using data analysis techniques consisting of data condensation, data presentation, and drawing conclusions. The results showed that the online learning process during the Covid-19 Pandemic at the Office Administration Education Study Program, Faculty of Social Sciences and Law, Makassar State University was effective. Thus, it can be concluded that online learning during the Covid-19 Pandemic at the Office Administration Education Study Program, Faculty of Social Sciences and Law, Makassar State University has been effective. This research can be used as a reference material in improving the teaching and learning process at the study program level because this research focuses on the effectiveness of online learning.